The middle cerebral artery density and ratio for the diagnosis of acute ischaemic stroke in the Emergency Department - AKOĞLU, HALDUN (WILEY, 2021)
Purpose Non-contrast computed tomography (ncCT) is the first-line imaging modality for acute ischaemic stroke diagnosis. Recognition of the early diagnostic signs of a stroke on computed tomography (CT) is crucial. The hyperdense middle cerebral artery (MCA) sign is one of these findings. We investigated the diagnostic utility of absolute MCA density (MCAD) in patients with acute MCA stroke confirmed with diffusion-weighted magnetic resonance imaging (dwMRI). Methods We retrospectively included all patients who presented to the Emergency Department with symptoms related to an acute stroke and confirmed with a dwMRI and ncCT to this diagnostic case-control study. An expert radiologist with more than four years of experience in neuroradiology re-evaluated all ncCT images. The evaluation of MCAD and ratio were measured on axial images in Hounsfield units (HU). Results We included 407 patients in our study (MCA infarction: 55%, n = 225; Control: 45%, n = 182). We calculated the threshold for the highest sensitivity (20%) and specificity (94%) as 49 HU with the Youden J index test for MCAD and as 1.1 for MCAD ratio (sensitivity 20% and specificity 95%). MCAD >49 HU or MCAD ratio >1.1 alone or joint use of MCAD >47 HU and MCAD ratio >1.1 are useful markers to confirm the diagnosis of MCA AIS with a specificity of at least 94%. Higher MCAD values are associated with larger infarction volumes. Conclusion MCAD and MCAD ratio can be used to identify patients who need early treatment, especially in situations where computed tomography angiogram or dwMRI are not readily available.
Keywords: COMPUTED-TOMOGRAPHY; SIGN; CT; THROMBOLYSIS; RELIABILITY; SENSITIVITY